The origins of war : a Catholic perspective - Shadle, Matthew Allen, 1979- (Moral traditions series., 2011)
Debate rages within the Catholic Church about the ethics of war and peace, but the simple question of why wars begin is too often neglected. Catholics' assumptions about the causes of conflict are almost always drawn uncritically from international relations theory -- a field dominated by liberalism, realism, and Marxism -- which is not always consistent with Catholic theology. In The Origins of War, Matthew A. Shadle examines several sources to better understand why war happens. His retrieval of biblical literature and the teachings of figures from church tradition sets the course for the bo.